Carbon Offset Legal Regulatory Model as a Source of Conservation-Based Tourism Financing in Indonesia - Niza Wibyana Tito; Yessy Madya Putri (Ann Publisher, 2026)
Background. Sustainable tourism development demands a balance between economic growth and nature conservation. Unfortunately, conservation funding in Indonesia is still heavily dependent on limited state budgets. The carbon offset mechanism emerged as an alternative to bridge the ecological responsibility of the tourism industry and the needs of environmental financing. Purpose. This normative legal research aims to examine the development of carbon laws and to formulate an ideal model for conservation tourism. Method. By examining various regulations, such as Law No. 10/2009 and Presidential Regulation No. 98/2021, an irony emerged: the legal basis for carbon economics already exists, but it has not been integrated into the tourism sector. This gap leads to norm vacancies, rule insynchronization, and weak implementation. Results. As a solution, this research proposes a